Gas chromatography - Poole, C. F. (Elsevier, 2012)
"This title provides comprehensive coverage of modern gas chromatography including theory, instrumentation, columns, and applications addressing the needs of advanced students and professional scientists in industry and government laboratories. Chapters are written by recognized experts on each topic. Each chapter offers a complete picture with respect to its topic so researchers can move straight to the information they need without reading through a lot of background information. Individual chapters written by recognized experts -- The big picture of gas chromatography from theory, to methods, to selected applications -- Provides references to other sources in associated areas of study to facilitate research -- Gives access to core data for practical work, comparison of results and decision making."--Publisher's description.